Hybrid control mechanism-based DVR for mitigation of voltage sag and swell in solar PV-based IEEE 33 bus system - Sowmyashree Narayana Setty; Mysore Subbakrishna Deekshit Shashikala; Kalyan Thippeswamy Veeramanju (Institute of Advanced Engineering and Science, 2023)
The power quality issues are raised due to sag/swell, which affects the overall performance of the grid-connected system. This study introduces the hybrid control mechanism based on a dynamic voltage restorer (DVR) to mitigate the sag and swell issues in the solar PV-based IEEE 33 bus system. The hybrid controller improves the dynamic performance and boosts the overall efficiency of the DVR system. The proposed work is also used to address the distribution system's voltage quality issues with minimal energy drawn out from the utility grid and effectively use solar energy. The sag and swell are introduced at the grid side and compensated at the load side by injecting DVR voltage. The proportional-integral (PI) controller followed by the fuzzy logic controller (FLC) is used to create the hybrid control mechanism for DVR. In this work, the solar PV system with DVR system is connected to the 29th location in the IEEE 33 bus system for performance realization. The hybrid control mechanism-based DVR provides 1.06% and 1.05% total harmonic distortion (THD) at sag and swell conditions for load voltage. The proposed work meets the IEEE 519 standards in terms of THD calculation. The proposed design compares with existing work and shows better THD reduction for load voltages.